2007
DOI: 10.1007/s10620-007-9977-z
|View full text |Cite
|
Sign up to set email alerts
|

A New Rat Model Links Two Contemporary Theories in Irritable Bowel Syndrome

Abstract: Acute infection with C. jejuni 81-176 precipitates alterations in stool consistency, bacterial overgrowth and rectal lymphocytosis consistent with findings in IBS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 25 publications
2
54
0
Order By: Relevance
“…15 In addition to acute diarrhea, C. jejuni is associated with a number of post infectious serious sequelae, including Guillain-Barré syndrome (GBS), 16 reactive arthritis 17 , and irritable bowel syndrome (IBS). 3,18 Moreover, an association of repeated C. jejuni infections with malnutrition has been reported in the developing world. 19,20 The molecular basis for the association of C. jejuni with GBS is recognized to be due to the mimicry between lipooligosaccharide (LOS) chains of most C.jejuni strains, such that antibodies directed toward LOS cross react with human peripheral nerves.…”
Section: Introductionmentioning
confidence: 99%
“…15 In addition to acute diarrhea, C. jejuni is associated with a number of post infectious serious sequelae, including Guillain-Barré syndrome (GBS), 16 reactive arthritis 17 , and irritable bowel syndrome (IBS). 3,18 Moreover, an association of repeated C. jejuni infections with malnutrition has been reported in the developing world. 19,20 The molecular basis for the association of C. jejuni with GBS is recognized to be due to the mimicry between lipooligosaccharide (LOS) chains of most C.jejuni strains, such that antibodies directed toward LOS cross react with human peripheral nerves.…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms of campylobacteriosis can range from a mild, watery diarrhea to dysentery, often with abdominal pain and fever (1). Moreover, there are several serious postinfectious complications associated with C. jejuni, including reactive arthritis (38), Guillain-Barré syndrome (2), and irritable bowel syndrome (35,44).…”
mentioning
confidence: 99%
“…Although symptoms of PI-IBS after bacterial infection in humans have been widely studied, no valid animal models were developed until recent studies showed that infection with Campylobacter jejuni leads to altered stool consistency after the acute gastroenteritis phase, and that this infection appears to precipitate bacterial overgrowth in 27% of exposed rats with rectal lymphocytosis [12]. This characteristic matches the phenomenon where IBS patients have bacterial overgrowth in the small intestine [64,65].…”
Section: Bacterial Infectionmentioning
confidence: 99%
“…Based on the current understanding of PI-IBS, in an ideal animal model, the animals should not only completely recover from the acute intestinal infection or inflammation but also show intestinal features such as visceral hypersensitivity, motility dysfunction, and changes in permeability or secretion. There are several types of PI-IBS models; some are based on intestinal infection (post-infection), and some are based on chemical agent-induced inflammation (post-inflammation), but all mimic one or more features of IBS [11][12][13][14][15][16][17]. This study reviewed the animal models of PI-IBS in the literature, and assessed the strengths and weaknesses of these models.…”
Section: Introductionmentioning
confidence: 99%